EFEKTIFITAS HUKUM PENYELESAIAN PERKARA KECELAKAAN LALU LINTAS MELALUI RESTORATIVE JUSTICE - Agus Wicaksono Susanto; Maryano, Maryano; Hedwig Adianto Mau (Journal of Innovation Research and Knowledge, 2025)
Normatively, Law Number 22 of 2009 on Road Traffic and Transport has comprehensively regulated various provisions that must be adhered to by the offender in traffic accidents involving victims. In the context of traffic accidents, if the accident is caused by culpa levis, it can be resolved through a restorative justice approach. This research utilizes the theory of restorative justice and the theory of legal effectiveness. This research falls into the category of empirical legal research, using two approaches simultaneously, namely the statute approach and the case approach. The legal materials in this research were obtained from primary and secondary data, consisting of primary legal materials, secondary legal materials, and tertiary legal materials. In this research, the results obtained from primary and secondary data were further analyzed. The data analysis process was conducted using an interpretative approach. The research results indicate that the concept of restorative justice in the settlement of traffic accident cases in Indonesia has been applied in various law enforcement agencies, including the Police, the Prosecutor's Office, and the Courts. In the stages of investigation and inquiry, the Police refer to the Chief of Police Regulation Number 8 of 2021, the Prosecutor's Office follows the Prosecutor General Regulation Number 15 of 2020, and the Court refers to the Supreme Court Regulation Number 1 of 2024. Although these regulations are binding for each agency, their implementation remains separate, which leads to the potential for differing interpretations among law enforcement agencies, affecting the justice process received by both the offender and the victim. The effectiveness of settling traffic accident cases through restorative justice has proven to be effective in resolving disputes peacefully, especially in cases of unintentional negligence. However, voluntary participation from both parties is crucial to its success. Although restorative justice has been applied in several cases in court, its implementation in Indonesia is not yet uniform and consistent. Certain cases, particularly those involving accidents with fatalities, still end in prison sentences.